2015
DOI: 10.1371/journal.pone.0125186
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between Adiponectin Gene Polymorphisms and Late-Onset Alzheimer’s Disease

Abstract: In recent years, researchers have found that adiponectin (ANP) plays an important role in the pathogenesis of Alzheimer's disease (AD), and low serum concentrations of ANP are associated with AD. Higher plasma ANP level have a protective effect against the development of cognitive decline, suggesting that ANP may affect AD onset. Meanwhile, accumulating evidence supports the crucial role of ANP in the pathogenesis of AD. To study the relationship between ANP gene polymorphisms (rs266729, -11377C>G and rs150129… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
(26 reference statements)
0
17
1
Order By: Relevance
“…Within this framework, the mechanistic actions of APN in AD could be considered. In support of this idea, it is noteworthy that polymorphisms of the APN gene have recently been linked to sporadic AD 65, 66…”
Section: Apn As a Novel Target For Therapies For Admentioning
confidence: 89%
“…Within this framework, the mechanistic actions of APN in AD could be considered. In support of this idea, it is noteworthy that polymorphisms of the APN gene have recently been linked to sporadic AD 65, 66…”
Section: Apn As a Novel Target For Therapies For Admentioning
confidence: 89%
“…Meanwhile, another clinical study demonstrated that decreased serum APN level is associated with mild cognitive impairments and AD [34]. A recent publication reported that polymorphisms in the APN gene locus were associated with higher risk of AD [32]. Although it is believed that APN crosses the BBB from the systemic circulation to the CNS, the changes of circulatory APN level may not reflect the changes of APN level in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous findings demonstrated APN to be protective against Aβ neurotoxicity [31]. Although a recent publication showed an association between APN gene polymorphism and late onset AD [32], there are contradictory clinical reports on the difference of plasma APN level between non-demented control and AD or mild cognitive impairment patients [3335]. The role of APN in AD remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to previous findings, another report showed no significant difference of adiponectin levels between a non-demented group and patients with dementia [80]. Furthermore, Yu et al found correlations between adiponectin gene polymorphism and late onset AD [81]. Two studies reported on low adiponectin levels in T2DM patients who had reduced gray matter volume, hippocampal volume and glucose metabolism, to be consistent with Alzheimer’s disease pathophysiologies [79,82].…”
Section: Pathophysiological Roles Of Adiponectin In Alzheimer’s DImentioning
confidence: 96%